Pemanfaatan Software Desain untuk Pembuatan Media Promosi UMKM Kota Medan - Simson Panjaitan; Renal Oktra Surbakti; Reynaldi Emit Simanjuntak; Christine Tamba; Komda Saharja (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
Promotion media is a means used in supporting promotion activities and the introduction of products or services to the community, so that when doing promotion media can increase the income of a product or service. The purpose of this Scientific Writing is to increase knowledge for people MSMEs of Medan City to create various designs such as banners, pamphlets, logos, and brochures using Adobe Photoshop CS6 Software. From the results of the analysis that the people of MSMEs of Medan City can be given design training to be able to make their own all promotions of products and services using Adobe Photoshop CS6 Software, because their use is easy to understand for beginners and can be developed more optimally according to ability.